Remembering the Memphis Massacre: an American story - Bond, Beverly Greene; O'Donovan, Susan E. (The University of Georgia Press, 2020)
"On May 1, 1866, a minor exchange between (white) Memphis city police and a group of (all black) Union soldiers quickly escalated into "murder and mayhem." A mob of white men roamed through south Memphis, leaving a trail of blood, rubble, and terror in their wake. By May 3, at least forty-six African American men, women, and children and two white men lay dead. Other Memphians, mostly black but a few whites closely associated with the city's growing population of black migrants, lost their homes. Many were brutally assaulted. An unknown number of terrified blacks were driven out of the city. Every African American church and schoolhouse lay in ruins, homes and businesses burglarized and burned, and at least five women had been raped. As a federal military commander noted in the days following, "What [was] called the 'riot,'" was "in reality [a] massacre" of extended proportions. Remembering the Memphis Massacre is a collection of essays that will teach non-specialists about a history that has been hidden from all but academics for most of the past century and a half, thereby placing the Memphis Massacre in its wider historical context"--